How can cryptocurrency and blockchain technology play a role in building social and solidarity finance? - Brett Scott (United Nations Research Institute for Social Development (UNRISD), 2016)
The decentralized digital currency Bitcoin - and its underlying "blockchain" technology - has created much excitement in the technology community, but its potential for building truly empowering social and solidarity-based finance has yet to be tested. This paper provides a primer on the basics of Bitcoin and discusses the existent narratives about the technologys potential to facilitate remittances, financial inclusion, cooperative structures and even micro-insurance systems. It also flags up potential points of concern and conflict; such as the tech-from-above "solutionism" and conservative libertarian political dynamics of some of the technology start-up community that surrounds Bitcoin. As a way of contrast the paper considers "blockchain 2.0" technologies with more overtly communitarian ideals and their potential for creating "cooperation at scale". It concludes with suggestions for future research.
Keywords: 330